A Cross-Sectional Study on the Relationship Among Cytokines, 5-HT2A Receptor Polymorphisms, and Sleep Quality of Non-manual Workers in Xinjiang, China - Wang, Juan; Gao, Xiaoyan; Gao, Pengcheng; Liu, Jiwen (Frontiers in Psychiatry, 2022)
Background: Studies have shown that cytokine activity changes during the sleep-wake process, suggesting that inflammatory factors may be involved in a mechanism affecting sleep quality. In addition, the serotonergic system is an important component of airway relaxation during sleep, especially the type in which serotonin 2A receptor (5-HTR2A) plays an important role in the sleep-wake process. Therefore, we aimed to investigate the effects of cytokines and 5-HTR2A polymorphisms on sleep in non-manual workers in Urumqi, Xinjiang in order to explore the relationship among the three. Methods: A total of 1,500 subjects selected using cluster random sampling participated in a cross-sectional survey, and 1,329 subjects were included in the questionnaire study based on the inclusion and exclusion criteria. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index questionnaire. Another 15% of the survey subjects were randomly selected for the experimental study group. The polymerase chain reaction-restriction fragment length polymorphism was used to detect 5-HTR2A gene genotypes. The cytokine (IL-1β, IL-2, IL-6, and TNF-α) content was evaluated using an enzyme-linked immunoassay. Results: The results showed that among 1,329 respondents, 870 had sleep quality problems. The detection rate was 65.46%. The distribution of -1438G/A genotypes in the 5-HTR2A gene was significantly different among different sleep quality groups (p < 0.05), with no statistical significance present when comparing to T102C (p > 0.05). A forest plot showed that the AG (odds ratio (OR) =2.771, 95% confidence interval (CI): 1.054–7.287) and GG (OR=4.037, 95%CI: 1.244–13.105) genotypes at -1438G/A loci were both associated with poor sleep quality and were thus considered the susceptibility genotypes for sleep problems. Furthermore, IL-1β was shown to be a protective factor for sleep quality (OR=0.949, 95%CI: 0.925–0.974). The interaction results showed that AG×IL-1β (OR=0.952, 95%CI: 0.918–0.987) was associated with a lower risk of sleep problems than AA×IL-1β.